“Sandwich” Strategy to Intensify EGFR Blockade by Concurrent Tyrosine Kinase Inhibitor and Monoclonal Antibody Treatment in Highly Selected Patients - Zhang, Guoqing; Yan, Beibei; Guo, Yanan; Yang, Hang; Li, Jindong (Frontiers in Oncology, 2022)
EGFR TKIs are not curative, and targeted resistance inevitably results in therapeutic failure. Additionally, there are numerous uncommon EGFR mutations that are insensitive to EGFR TKIs, and there is a lack of clinical strategies to overcome these limitations. EGFR TKI and mAbs target EGFR at different sites, and a combination regimen for delaying/preventing resistance to targeted therapy or obtaining more intensive inhibition for uncommon mutations at cellular, animal and human levels has been explored. This review critically focuses on a combination strategy for uncommon EGFR mutation-positive NSCLC, and discuss the preclinical data, clinical implications, limitations and future prospects of the combination strategy.